2015
DOI: 10.1007/s10195-015-0348-9
|View full text |Cite
|
Sign up to set email alerts
|

Does the position of shoulder immobilization after reduced anterior glenohumeral dislocation affect coaptation of a Bankart lesion? An arthrographic comparison

Abstract: BackgroundThe position of immobilization after anterior shoulder dislocation has been a controversial topic over the past decade. We compared the effect of post-reduction immobilization, whether external rotation or internal rotation, on coaptation of the torn labrum.Materials and methodsTwenty patients aged <40 years with primary anterior shoulder dislocation without associated fractures were randomized to post-reduction external rotation immobilization (nine patients) or internal rotation (11 patients). Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The immobilization position is usually the so called standard (IR, neutral F and ABD with elbow 90º F), however in 2003 a new method of immobilization in external rotation was described by Japanese authors which revealed that this position can reduce significantly the rate of recurrence [ 30 ]. These findings were recently confirmed by two other studies [ 31 , 32 ] On the other hand it seems that the length of the immobilization period does not affect the rate of recurrence [ 23 ].…”
Section: How Does the Disease Evolve Without Surgical Treatment?supporting
confidence: 73%
“…The immobilization position is usually the so called standard (IR, neutral F and ABD with elbow 90º F), however in 2003 a new method of immobilization in external rotation was described by Japanese authors which revealed that this position can reduce significantly the rate of recurrence [ 30 ]. These findings were recently confirmed by two other studies [ 31 , 32 ] On the other hand it seems that the length of the immobilization period does not affect the rate of recurrence [ 23 ].…”
Section: How Does the Disease Evolve Without Surgical Treatment?supporting
confidence: 73%
“…Copyrights @ Arrisna Artha, et al Orthop & Spo Med Op Acc J 504 capsule detachment and labral lesions [1,2,17,32]. Regarding to its superiority, some studies also reported the conflicting results on patients' acceptance to use external rotation brace [23]. In 2010, Paterson, et al made an analysis for preference duration of immobilization in primary anterior shoulder dislocation.…”
Section: Volume 5 -Issuementioning
confidence: 99%
“…In this study, the positive influence on reduction of anterior hematoma in ER was also confirmed for 75% of the patients [ 32 ]. In a recent study, Momenzadeh et al confirmed in MR arthrography decreased separation in patients immobilized for 3 weeks in ER when compared to a group immobilized in IR, a difference that reached statistical significance [ 33 ]. Chetouani et al achieved migration of hematoma towards the posterior pouch in all 15 shoulders immobilized in ER.…”
Section: Imaging Studiesmentioning
confidence: 99%